(untitled) (Journal of Asian Development Studies, 2024)
This study investigates the comparative study which concentrates on the impact of the two types of feedback: recast vs. metalinguistic, as an intervention in second language writing in English in Pakistan to reduce error essay writing. Written corrective feedback is a process which is introduced by educationists and psychologists which attracts the attention of the learner and stimulates him to improve his cognition by the direction given by teachers. Mixed method is used to evaluate the effect of these two types of feedback at intermediate level in Pakistan. Quasi experimental method was used to evaluate the development of the student in the destined writing by using test in the form of pre-test and post-test. The problems which are persisted in the text are exposed in the interviews that had paid little attention to the feedback comments. The collected data is analyzed through Statistical Package for Social Sciences. The finding reveals an overall effect indicating the written corrective feedback has a potential to enhance the second language writing grammatical accuracy. The results of this study highlights that metalinguistic feedback is more efficacious than its near counterpart recast.